Out of the South? The first Afrotropical record of Prochyliza Walker (Diptera: Piophilidae), with description of a new species - Martín-Vega, Daniel; Ebejer, Martin J.; Whitmore, Daniel (Zootaxa, 2017)
The genus Prochyliza Walker is recorded for the first time from the Afrotropical Region. A new species, Prochyliza ignifera sp. nov., is described from the Indian Ocean islands of Aldabra and La Réunion. The status of this species as possibly the most primitive in the genus Prochyliza is hypothesised and discussed, raising some questions about the taxonomy and the zoogeographical origin of the group. The holotype of Piophila viridicollis Macquart from La Réunion was studied and it is instated as a subjective junior synonym of Piophila casei (Linnaeus), syn. nov.